The Epidemiology of pertussis in the Australian Capital Territory, 1999 to 2005—epidemics of testing, disease or false positives? - Wylks, Clare E; Ewald, Ben; Guest, Charles (Communicable Diseases Intelligence, 2007)
The increase in pertussis notifications since the 1990s in many countries, including Australia, has been attributed to improved diagnosis. This study aimed to describe the epidemiology of pertussis in the Australian Capital Territory from 1999 to 2005, determine whether the apparent changes could be accounted for by greater recognition and testing, and explore the impact of false positive serology results associated with faulty test kits. The Australian Capital Territory resident notification, laboratory and separation data from 1999 to 2005 were examined and the proportions of positive tests across time periods and age groups compared. Notification rates increased in the years 2000, 2003 and 2005. There was a shift in the age distribution of cases, from children and teenagers in 2000, to teenagers in 2003 and adults in 2005. Testing activity and notification activity were closely related. Comparing the epidemic periods to the preceding inter-epidemic periods, the proportion of positive tests was maintained or increased for all age groups combined and for adults and children (e.g. statistically significant increase from 7.8% to 14.0% in the 2005 epidemic in adults). During each epidemic the proportion of positive tests was statistically significantly higher in the age group with the highest notification activity. Despite similar testing rates in adults in 2003 and 2005, greater disease activity was reported in 2005. Although the numbers were small, polymerase chain reaction and culture positive test results increased in 2003 but not in 2005. The proportion of positive polymerase chain reaction results increased in 2003, providing strong evidence that the apparent epidemic of 2003 was due to a true increase in underlying disease activity. Because of the uncertainty surrounding the timing of the false positive serology results, the study provides weaker support for a true epidemic of pertussis in 2005. Commun Dis Intell 2007;31:383–391.